DEVELOPMENT OF THERMAL MANAGEMENT TECHNOLOGY ON BRICK WALL FACADES FOR URBAN HEAT ISLAND INTENSITY MITIGATION - Ornam, Kurniati
The escalating phenomenon of increased air temperatures in urban areas, commonly referred to as the urban heat island (UHI), is intricately linked to the thermal properties of building facades within these regions. Heavy building materials, such as brick, exhibit distinct thermal behaviors compared to other materials. In the morning, brick walls absorb heat from solar radiation and tend to retain and store it. During the day, this accumulated heat is released into the surrounding area, contributing to an elevation in air temperature. Subsequently, in the evening, the brick walls reabsorb heat, particularly on the western side, releasing it at night, thus inducing localized heating and an increase in urban heat island intensity (UHII).